2018
DOI: 10.1002/ijc.31900
|View full text |Cite
|
Sign up to set email alerts
|

CA19‐9 and apolipoprotein‐A2 isoforms as detection markers for pancreatic cancer: a prospective evaluation

Abstract: Recently, we identified unique processing patterns of apolipoprotein A2 (ApoA2) in patients with pancreatic cancer. This study provides a first prospective evaluation of an ApoA2 isoform (“ApoA2-ATQ/AT”), alone and in combination with carbohydrate antigen 19-9 (CA19-9), as an early detection biomarker for pancreatic cancer. We performed ELISA measurements of CA19-9 and ApoA2-ATQ/AT in 156 patients with pancreatic cancer and 217 matched controls within the European EPIC cohort, using plasma samples collected up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 27 publications
6
41
2
Order By: Relevance
“…Some studies considered that the independent risk predictors of postoperative serum CA19-9, CA125, and CEA indicated poor surgical outcome in pancreatic ductal adenocarcinoma [34]. CA 19-9 is a good indicator for the screening of pancreatic cancer [35] but was not a good predictor of selection for RPD in our study. This is probably because the levels of CA 19-9 are evaluated in most pancreatic ductal adenocarcinoma patients.…”
Section: Discussioncontrasting
confidence: 57%
“…Some studies considered that the independent risk predictors of postoperative serum CA19-9, CA125, and CEA indicated poor surgical outcome in pancreatic ductal adenocarcinoma [34]. CA 19-9 is a good indicator for the screening of pancreatic cancer [35] but was not a good predictor of selection for RPD in our study. This is probably because the levels of CA 19-9 are evaluated in most pancreatic ductal adenocarcinoma patients.…”
Section: Discussioncontrasting
confidence: 57%
“…Blood tests of apoA2-ATQ/AT might thus be useful for efficiently identifying subjects who should undergo imaging examinations, such as CECT, MRCP or EUS. Furthermore, our latest cohort study indicated that PC might be predictable up to 18 months prior to diagnosis by examining levels of apoA2-i [ 19 ]. These findings indicate that screening for PC by measuring the plasma apoA2-ATQ/AT level and then performing imaging examinations in appropriate cases could prove effective.…”
Section: Discussionmentioning
confidence: 99%
“…Our latest study reported that biomarkers used to detect PC should provide sensitivity at least 15 times higher than the false-positive rate (e.g., 30% sensitivity with 98% specificity) [ 19 ]. In our prospective screening study, the plasma apoA2-ATQ/AT cut-off level was provisionally set at 35 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Honda (26) ApoA2-ATQ levels seem to reflect pancreatic atrophy and insufficient secretion of circulating pancreatic enzymes.…”
Section: Blood-based Biomarkers For Early Detection Of Pdacmentioning
confidence: 99%
“…In this blinded study, AUCs for CA19-9 and apoA2-ATQ /AT as single biomarkers to distinguish patients with early-stage pancreatic cancer (stage-I/II) were 0.783 (95% confidence interval (CI), 0.699-0.855) and 0.809 (95%CI, 0.748-0.867), respectively [25]. In addition, plasma samples collected by the European Prospective Investigation into Cancer and Nutrition study have been investigated, revealing that combination assay with CA19-9 and apoA2-ATQ/AT enabled earlier detection of PDAC than CA19-9 alone up to 18 months before diagnosis [26]. Such findings suggest apoA2 isoforms as potential biomarkers for filtering the general population for individuals at higher risk of PDAC.…”
Section: Blood-based Biomarkers For Early Detection Of Pdacmentioning
confidence: 99%